Common Interaction Surfaces of the Toll-Like Receptor 4 Cytoplasmic Domain Stimulate Multiple Nuclear Targets - Ronni, Tapani (American Society for Microbiology, 2003)
Toll-like receptor 4 (TLR4) mediates the host response to lipopolysaccharide (LPS) by promoting the activation of pro- and anti-inflammatory cytokine genes. To activate each gene, numerous signal transduction pathways are required. The adaptor proteins MyD88 and TIRAP contribute to the activation of several and possibly all pathways via direct interactions with TLR4's Toll/interleukin-1 receptor (IL-1R) (TIR) domain. However, additional adaptors that are required for the activation of specific subsets of pathways may exist, which could contribute to the differential regulation of target genes. Furthermore, it remains unknown whether direct interactions that have been reported between TIR domains and other proteins are required for TLR4 signaling. To address these issues, we systematically mutated the TLR4 TIR domain in the context of a CD4/TLR4 fusion protein. Several exposed residues defining at least two structural surfaces were required in macrophages for activation of the proinflammatory IL-12 p40 and anti-inflammatory IL-10 promoters, as well as promoters dependent on individual transcription factors. Interestingly, the same residues were required by all promoters tested, suggesting that the signaling pathways diverge downstream of the adaptors. The mutant phenotypes provide a framework for future studies of TLR4 signaling, as the interaction supported by each critical surface residue will need to be defined.